Gælden, gaven og geden: Om skyldnere og humanitær økonomi - Sharma, Devika (K&K - Kultur og Klasse, 2018)
This article centers on the complex relationship between debt and gifts – or, more to the point, between the neoliberal economy of debt as diagnosed by Maurizio Lazzarato, among others, and humanitarian subjectivity; Between debt government and humanitarian government. Drawing on the work of Ananya Roy and looking to objects of debt/humanitarian relief such as Greece and Haiti, I suggest that what Lazzarato terms ‘indebted man’ today co-exists in hitherto unexamined ways with ‘humanitarian man’, and that these two forms of subjectivity in fact share dispositions of guilt and shame. In order to further examine the guilty or ‘indebted’ disposition of everyday humanitarians I then continue to discuss a particular humanitarian product, namely the ‘charity goat’ and other third-party gifts. Here I draw in particular on Lilie Chouliaraki’s notion of post-humanitarianism in order to suggest that third-party charitable giving gives cultural form to the experience of indebtedness of the humanitarian gift-giver. This experience is, I finally suggest, part of a broader Scandinavian, but not exclusively Scandinavian, predicament of privilege.